Two new endemic species of Epictia Gray, 1845 (Serpentes: Leptotyphlopidae) from Northern Peru - Koch, Claudia; Cruz, Roy Santa; Cárdenas, Heidy (Zootaxa, 2016)
Herein, we describe two new thread snake species of the genus Epictia from elevations higher than 2000 meters above sea level in the Andes of the Cajamarca Region in Northern Peru. Both species share 10 midtail scale rows, a broad contact between the anterior supralabial and the supraocular scales in most of the specimens, and a yellow spot on the snout and the terminal part of the tail. Epictia venegasi sp. nov. is described on the basis of nine specimens and can further be differentiated from its congeners by having 211–221 mid-dorsal scale rows and a color pattern where each body scale is black on the anterior half and yellow on the posterior half. The description of Epictia vonmayi sp. nov. is based on two specimens which can further be differentiated from their congeners by having 196–205 mid-dorsal scale rows and 14 distinct black longitudinal stripes around the body, which run through the center of each scale and are separated by bright yellow interspaces; accordingly the tail exhibits 10 black longitudinal stripes which likewise run through the center of each scale.